The Role of Vanadium in Metallodrugs Design and Its Interactive Profile with Protein Targets - Otávio Augusto Chaves; Francisco Mainardi Martins; Carlos Serpa; Davi Fernando Back (Future Pharmacology)
Metallodrugs represent a critical area of medicinal chemistry with the potential to address a wide range of diseases. Their design requires a multidisciplinary approach, combining principles of inorganic chemistry, pharmacology, and molecular biology to create effective and safe therapeutic agents. Vanadium, the element of the fifth group of the first transition series (3d metals), has been already detected as a crucial species in the biological action of some enzymes, e.g., nitrogenases and chloroperoxidase; furthermore, vanadium-based compounds have recently been described as physiologically stable with therapeutic behavior, e.g., having anticancer, antidiabetic (insulin-mimicking), antiprotozoal, antibacterial, antiviral, and inhibition of neurodegenerative disease properties. Since the binding of metallodrugs to serum albumin influences the distribution, stability, toxicity (intended and off-target interactions), and overall pharmacological properties, the biophysical characterization between serum albumin and vanadium-based compounds is one of the hot topics in pharmacology. Overall, since vanadium complexes offer new possibilities for the design of novel metallodrugs, this review summarized some up-to-date biological and medicinal aspects, highlighting proteins as the main targets for the inorganic complexes based on this transition metal.